Deciphering the Multi-tiered Regulatory Network That Links Cyclic-di-GMP Signaling to Virulence and Bacterial Behaviors - (:unkn) unknown (My University, 2016)
Bis-(3’-5’)-cyclic dimeric guanosine monophosphate (c-di-GMP) is a bacterial second messenger that regulates multiple cellular behaviors in most major bacterial phyla. C-di-GMP signaling in bacterial often includes enzymes that are responsible for the synthesis and degradation of c-di-GMP, effector proteins or molecules that bind c-di-GMP, and targets that interact with effectors. However, little is known about the specificity of c-di-GMP signaling in controlling virulence and bacterial behaviors. In this work, we have investigated the c-di-GMP signaling network using the model plant pathogen Dickeya dadantii 3937. In Chapter 2, we characterized two PilZ domain proteins that regulate biofilm formation, swimming motility, Type III secretion system (T3SS) gene expression, and pectate lyase production in high c-di-GMP level conditions. YcgR3937 binds c-di-GMP both in vivo and in vitro. Next, we revealed a sophisticated regulatory network that connects the sRNA, c-di-GMP signaling, and flagellar master regulator FlhDC. We proposed FlhDC regulates T3SS through three distinct pathways, including the FlhDC-FliA-YcgR3937 pathway; the FlhDC-EcpC-RpoN-HrpL pathway; and the FlhDC-rsmB-RsmA-HrpL pathway. Genetic analysis showed that EcpC is the most dominant factor for FlhDC to positively regulate T3SS expression. In chapter 3, we constructed a panel of single-deletion mutants, in which each GGDEF and/or EAL domain protein coding gene was individually either deleted or inactivated. Various cellular outputs were investigated using these mutants. We showed that GGDEF domain protein GcpA negatively regulates swimming motility, pectate lyase production, and T3SS gene expression. GcpD and GcpL only negatively regulate the expression of T3SS and swimming motility but not the pectate lyase production.